CLINICAL-NEUROLOGICAL AND NEUROPHYSIOLOGICAL CHANGES IN CHILDREN WITH TRISOMY OF CHROMOSOME 21 (Herald of the National Children's Medical Center, 2022)
Down syndrome is the most common chromosomal pathology. It occurs when, as a result of a random mutation, another chromosome appears in the 21st pair. Often, children with Down syndrome (DS) and related disorders have a lower IQlevel, severe forms of stereotypical behavior.Aim: to study neurological conditions in children with DM. Conducting clinical neurological, neurophysiological andaudiological studies in 34 children (16 boys, 18 girls) with DM. The Stanford-Binet scale was used to determine the intellectualstatus of children with DM. The manifestation of autistic disorders, somatic pathology, lack of speech activity are unfavorable prognostic factors in children with DM.
Keywords: Down syndrome; neurological status; Stanford-Binet intelligence scale; children